Eksistensi Budaya Indonesia dalam Buku Ajar Materi Bahasa Arab Siswa SMP Islam Terpadu: Perspektif Pendidikan Multikultural - Muhimmatul Choiroh; Kamal Yusuf (Alfaz (Arabic Literatures for Academic Zealots), 2021)
Education, which is based on the integration of culture, is a key part of the learning process. The teaching material will always be part of the success of the teaching and learning process. School as an educational institution or institution is responsible for instilling multicultural education in students from an early age, which will give birth to a multi-cultural generation, so that the concept of multicultural education is very much in line with that applied in the world of education in Indonesia. The current study therefore looked at culture as a measuring instrument for the application of multiculturalism, and further explained the existence of Indonesian culture in Arabic teaching materials for grade VIII at junior high school. The method used in this research is qualitatively descriptive through the use of library research and content analysis. The aim of this study is to provide an overview of the integration of Indonesian culture in Arabic textbooks at junior high school. It also seeks to look at the values of cultural diversity that are embedded in students' attitudes towards multi-cultural education, such as respect for tolerance, fairness, democracy and respect for differences. The results of this study have placed a great deal of emphasis on the achievement of cultural competence, such as the integration of multicultural educational values at the visual level, images, people's names, places, and so on. However, the placement of cultural values that are substantive does not have enough place in the Arabic textbook. Keywords: Cultural Existence, Arabic Textbooks, Multicultural Education